Journey to the heart of the condor : love, loss, and survival in a South American dictatorship - Creigh, Emily C. (Peace Corps Writers, 2016)
Emily Creigh learned in November 1974 that she would spend the next two years and three months as a Peace Corps volunteer in Paraguay, a developing Latin American country with quaint customs and "tranquil" people. In fact, terror reigned in the US-backed banana republic with its "benevolent" dictator, Alfredo Stroessner, who had held the country in a state of siege for twenty years. The story of her stay in Paraguay is interwoven with the account of the imprisonment and torture of Dr. Martin Almada, doctor of education and director of a renowned school in Paraguay.